What is Impact of the August 2008 War to The Georgia’s Democratization Process - SERDAR, Zeynep TOPAL (COLLECTION OF SCIENTIFIC WORKS OF SOKHUMI UNIVERSITY, 2025)
The First Independent Republic of Georgia (1918-1921) can be said to be the first step taken by the Georgian nation towards democracy. In the late Soviet Georgian Republic, when the Georgian nation was intertwined with political phenomena, the consciousness of democratization reasserted itself. After the declaration of independence on April 9, 1991, a very traumatic period was entered politically, and preserving territorial integrity became a priority issue for the Georgians. In the early years of independence, the newly established Georgian state struggled with ethnic nationalist conflicts on the one hand and economic development on the other. As a matter of fact, the state-building process was delayed and institutional reforms were only possible in the 2000s. The road map of Georgia’s democratization process has been tried to be revealed. The August 2008 War is analyzed in terms of its impact on Georgia's democratization process. In this context, the impact of Russia’s policy to maintain its hegemony on Georgia is discussed. The aim of this study is to analyze the reform efforts in the state-building process in Georgia and to discuss the role of the Rose Revolution in this process.